Sleep HAPi: A Feasibility and Descriptive Analysis of an Early and Longitudinal Sleep Education Intervention for Pregnant Women. Issue 4 (4th July 2021) - Ladyman, Clare; Gander, Philippa; Huthwaite, Mark; Sweeney, Bronwyn; Signal, T. Leigh
ABSTRACT: Background : Poor sleep and prior depression are key predictors of perinatal depression, with research suggesting depressive symptoms may emerge in early pregnancy. Sleep is a potentially modifiable risk factor for depression. This pilot study examined the feasibility and acceptability of a six-month sleep education intervention designed to optimize sleep and minimize depressive symptoms throughout pregnancy. Sleep measures and depressive symptoms are described from 12 weeks gestation to 12 weeks postpartum. Participants : A community sample of nulliparous pregnant women with a history of depression were recruited prior to 14 weeks gestation. Methods : An individualized sleep education program was developed and participants engaged in three trimester specific sleep education sessions. Feasibility and acceptability were determined via recruitment and retention rates and participant feedback. Depressive symptoms and sleep were measured at five time points throughout the study. Results : 22 women enrolled in the study and 15 completed the intervention. Participants reported the intervention as highly acceptable. There was minimal change in all dimensions of sleep across pregnancy, but sleep measures were significantly worse at six weeks postpartum and improved by 12 weeks postpartum. Depressive symptoms were significantly lower at the conclusion of the intervention and 12 weeks postpartum compared to trimester 1. Conclusions : This sleep education program appears feasible, acceptable and may be effective in minimizing depressive symptoms in pregnant women with a history of depression. Trials with larger and more diverse samples are warranted and further studies to ascertain efficacy should be undertaken with a control group.